The Road Chronotope And the Experience of Displacement - Qodirova Maftuna Davron qizi (International Journal Of Literature And Languages, 2026)
This article examines the intersection of narrative space-time and human displacement through the lens of Mikhail Bakhtin’s concept of the chronotope, using John Steinbeck’s The Grapes of Wrath (1939) as its primary text. The analysis posits that Steinbeck transforms the quintessentially American road—specifically U.S. Highway 66—from a simple geographical setting into a complex chronotope that structures the experience of forced migration. By drawing on Bakhtin’s theory, this article argues that the road in The Grapes of Wrath functions not merely as a path for westward movement, but as a space where time is “thickened” and history is made tangible, fundamentally shaping the Joad family’s identity and their experience of dispossession. The analysis explores how the road chronotope becomes a crucible for community formation and ethical awakening, ultimately redefining the experience of displacement as a painful yet transformative suspension between a lost past and an uncertain future. It concludes that the chronotope of the road in The Grapes of Wrath serves as a critical narrative device for articulating the spatial and temporal disorientation inherent in the American refugee experience.